Strategi linguistik dalam kritik politik: Analisis wacana kritis bahasa kiasan pada stand-up comedy Indonesia - Ibrahim, Ibrahim; Absri, Absri; Rahmadani, Wilda (Universitas Mulawarman, 2025)
This study aims to analyze the role of humor, particularly in the form of stand-up comedy, as a medium of socio-political critique in Indonesia. The research data consist of thirteen excerpts from stand-up comedy monologues, analyzed using Critical Discourse Analysis with Fairclough’s model, which includes textual, discursive, and socio-cultural analysis. The study focuses on the use of figurative language such as metaphor, irony, paradox, and satire as discursive strategies to uncover hidden power relations embedded in political practices. The findings reveal that representations of professions such as foremen, laborers, project supervisors, and canteen workers are transformed into symbols that reflect structures of power, practices of nepotism, patronage, and injustices within the political system. Humor is shown to effectively expose serious issues such as political dynasties, structural inequalities, the erosion of meritocratic principles, and moral hypocrisy, presented in a manner that is light yet incisive.The stand-up comedy functions not only as entertainment but also as a counter-discourse that provides a safe, inclusive, and reflective space for society to critique political realities. The study concludes that humor plays a significant role in strengthening public awareness and can be regarded as a form of symbolic resistance against the status quo in contemporary democracy.